Arthrobacter enclensis sp. nov., isolated from sediment sample - Dastager, Syed Gulam; Qin, Liu; Tang, Shan-Kun; Krishnamurthi, Srinivasan; Lee, Jae-Chan; Li, Wen-Jun (Archives of Microbiology, 2014)
A novel bacterial strain designated as NIO-1008(T) was isolated from marine sediments sample in Chorao Island India. Cells of the strains were gram positive and non-motile, displayed a rod-coccus life cycle and formed cream to light grey colonies on nutrient agar. Strain NIO-1008(T) had the chemotaxonomic markers that were consistent for classification in the genus Arthrobacter, i.e. MK-9(H-2) (50.3 %), as the major menaquinone, and the minor amount of MK-7 (H-2-27.5 %), MK-8 (H-4-11.6 %) and MK-8 (H-2-10.4 %). anteiso-C-15:0, iso-C-15:0, iso-C-16:0 and C-15:0 were the predominant fatty acids. Galactose, glucose and rhamnose are the cell-wall sugars, and DNA G+C content was 61.3 mol%. Phylogenetic analysis, based on 16S rRNA gene sequencing, showed that the strains were most similar to Arthrobacter equi IMMIB L-1606(T), Arthrobacter chlorophenolicus DSM 12829(T), Arthrobacter defluvii KCTC 19209(T) and Arthrobacter niigatensis CCTCC AB 206012(T) with 98.5, 98.4, 98.0 and 97.8 %, respectively, and formed a separate lineage. Combined phenotypic data and DNA-DNA hybridization data supported the conclusion that strains NIO-1008(T) represent a novel species within the genus Arthrobacter, for which the name Arthrobacter enclensis sp. nov., is proposed. The type strain is NIO-1008(T) = (NCIM 5488(T) = DSM 25279(T)).
Keywords: Arthrobacter; Chorao Island; Marine sediment; Polyphasic